Obsidian from the Huluga Open Site and its Implications - Neri, Leee Anthony M. (Hukay, 2016)
Obsidian sourcing has great potential for providing information about mobility and exchange patterns in ancient times. The Huluga Open Site produced a considerable amount of obsidian artifacts and they were subsequently analyzed through X-ray Flourescence Spectroscopy (XRF) and Proton Induced X-ray Emmission/Proton Induced Gamma-ray Emmision (PIXE/PIGME). The chemical signature of the Huluga obsidian does not fit any known obsidian sources in the Philippines. It is therefore hypothesized that the obsidian materials from the Huluga Open Site were acquired through exchange with a source community outside of the Philippines.